1996
DOI: 10.1002/ana.410390314
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of horizontal and vertical eye movements in parkinsonian syndromes

Abstract: We studied dynamic properties of horizontal, vertical, and oblique eye movements in 23 patients with the following parkinsonian syndromes: idiopathic parkinsonism (PD), multiple system atrophy (MSA), pure akinesia (PA), progressive supranuclear palsy (PSP), and cortical-basal ganglionic degeneration (CBGD). Compared with age-matched controls, only PSP patients showed slowing of saccades. Patients in all groups showed saccadic hypometria that was most marked vertically. The trajectories of saccades made to diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
4
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 37 publications
12
119
4
1
Order By: Relevance
“…At onset, 33% showed such abnormalities (table 3). Studies of patients with CBS describe increased saccadic latency, [42][43][44][45] but this was not confirmed in a publication including oculographic measurements in 4 subjects with CBD, where 3 had visually guided saccades that were indistinguishable from normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…At onset, 33% showed such abnormalities (table 3). Studies of patients with CBS describe increased saccadic latency, [42][43][44][45] but this was not confirmed in a publication including oculographic measurements in 4 subjects with CBD, where 3 had visually guided saccades that were indistinguishable from normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…A couple of small studies have examined simple saccadic metrics in the horizontal, vertical, and diagonal planes in patients with PD, MSA, pure akinesia, PSP, 77 and CBD. 41 It was found that compared with age-matched controls only patients with PSP had slow saccades (in any direction), and only patients with CBD had increased saccadic latency. Other parameters such as hypometria, vestibuloocular responses, and smooth pursuit did not discriminate between groups, although deviation of oblique saccades towards the horizontal plane was more marked in patients with pure akinesia and PSP.…”
Section: Differential Diagnosismentioning
confidence: 96%
“…[39][40][41] This was initially demonstrated in saccades executed to verbal command, 42 in the dark, 43 or to fixed targets. 37 Predictive saccades also show hypometria, in addition to difficulty in anticipating the stimulus, 36,44 and in unilaterally affected patients the abnormalities were found to be lateralized.…”
Section: Research Findingsmentioning
confidence: 99%
“…Ocular motor abnormalities play an important role in differential diagnoses of Pick complex diseases [5,16,32,37]. Supranuclear gaze deficits among Pick complex diseases occur with PSP, CBD, and FTD.…”
Section: Introductionmentioning
confidence: 99%
“…Supranuclear gaze deficits among Pick complex diseases occur with PSP, CBD, and FTD. Many studies show slow saccades in PSP, especially in the vertical direction, even in early stages of the disease [32], a finding attributed to pathologic involvement of brainstem burst neurons [9,17,34]. Patients with CBD or FTD show relatively normal saccadic velocity but delayed initiation of saccades, which has been attributed to damage to cortical and subcortical structures for saccadic generation [5,32,37].…”
Section: Introductionmentioning
confidence: 99%